Development of Machine Learning for Debris Flow Event Prediction in a Volcanic Area - Ikhsan, Jazaul; Deng, Abraham Ayuen Ngong; Mohd Arif Zainol, M. R. R.; Ibrahim, Muhammad Shazril Idris; Miyata, Shusuke (Salehan Institute of Higher Education, 2026)
The integration of machine learning (ML) into debris flow prediction in volcanic areas, exemplified by the Gendol River watershed of Mount Merapi, offers transformative potential for hazard mitigation. This study aimed to develop real-time, computationally efficient ML models capable of integrating multi-source data, rainfall intensity of 25 mm/hour linked to 300 cm Debris Flow heights, antecedent precipitation, and geomorphological variables to predict debris flows with actionable lead times. Key objectives included optimizing prediction accuracy, minimizing the false positive rate to 18.2% for